Constructing Victims in the International Criminal Court: A Critical Discourse Analysis - Valerie King (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
The International Criminal Court (ICC) was established in 1998 to address serious crimes of concern to the international community, including genocide and crimes against humanity, among others. This paper examines the construction of victims in ICC proceedings. Through a critical discourse analysis of ICC web pages and other documents intended for victims, I argue that the ICC’s construction of victims reproduces criminal justice logics, which marginalize victims and denies them agency. Said marginalization occurs in an effort to balance retributive and restorative justice. Discourses concerning the role and agency of victims in the Court reproduce institutional neglect and disempowerment.